Control of there plenishment process for inventory management and its impacton the level of customer service in a mass merchandising company - Bravo Bayona, Rogger Arturo (2013)
This research details the analysis done to the replenishment process in one of the leading companies of the home centers sector in our country, through which improvements are defined to face the limitations found that show the replacement of goods as an unproductive activity. In this way, it seeks to contribute to better positioning the company against competition in a growing market like the current one. The necessary indicators were obtained to examine the evolution of the process in recent years, allowing demonstrate the hypothesis of correlation between the level of out-of-stock, representing replenishment timely management, and service level, which represents the end customer satisfaction and recognition for the company against the competition. Thus, in proposing a new model for the replenishment process is expected to optimize inventory management, increasing customer satisfaction and good image of the company.